Emissions Reduction Policies and Recent Trends in Southern California’s Ambient Air Quality - Lurmann, Fred (J Air Waste Manag Assoc, 2015)
To assess accountability and effectiveness of air regulatory policies, we reviewed over 20 years of monitoring data, emissions estimates, and regulatory policies across several Southern California communities participating in a long-term study of children’s health. Between 1994 and 2011, air quality improved for NO(2) and PM(2.5) in virtually all the monitored communities. Average NO(2) declined 28% to 53%, and PM(2.5) decreased 13% to 54%. Year-to-year PM(2.5) variability at lower-pollution sites was large compared to changes in long-term trends. PM(10) and O(3) decreases were largest in communities that were initially among the most polluted. Trends in annual average NO(2), PM(2.5), and PM(10) concentrations in higher pollution communities were generally consistent with NO(x), ROG, SO(x), PM(2.5), and PM(10) emissions decreases. Reductions observed at one of the higher PM(2.5) sites, Mira Loma, was generally within the range expected from reductions observed in ROG, NO(x), SO(x), and PM(2.5) emissions. Despite a 38% increase in regional motor vehicle activity, vigorous economic growth, and a 30% population increase, total estimated emissions of NO(x), ROG, SO(x), PM(2.5), and PM(10) decreased by 54%, 65%, 40%, 21%, and 15%, respectively, during the 20-year time period. Emission control strategies in California have achieved dramatic reductions in ambient NO(2), O(3), PM(2.5), and PM(10). However, additional reductions will still be needed to achieve current health-based clean air standards.